Cognitive, adaptive, and behavioral features in Joubert syndrome. Issue 12 (17th August 2016) - Bulgheroni, Sara; D'Arrigo, Stefano; Signorini, Sabrina; Briguglio, Marilena; Di Sabato, Maria Lucia; Casarano, Manuela; Mancini, Francesca; Romani, Marta; Alfieri, Paolo; Battini, Roberta; Zoppello, Marina; Tortorella, Gaetano; et al.
Abstract : Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterized by a distinctive cerebellar and brainstem malformation recognizable on brain imaging, the so‐called molar tooth sign. The full spectrum of cognitive and behavioral phenotypes typical of JS is still far from being elucidated. The aim of this multicentric study was to define the clinical phenotype and neurobehavioral features of a large cohort of subjects with a neuroradiologically confirmed diagnosis of JS. Fifty‐four patients aged 10 months to 29 years were enrolled. Each patient underwent a neurological evaluation as well as psychiatric and neuropsychological assessments. Global cognitive functioning was remarkably variable with Full IQ/General Quotient ranging from 32 to 129. Communication skills appeared relatively preserved with respect to both Daily Living and Socialization abilities. The motor domain was the area of greatest vulnerability, with a negative impact on personal care, social, and academic skills. Most children did not show maladaptive behaviors consistent with a psychiatric diagnosis but approximately 40% of them presented emotional and behavioral problems. We conclude that intellectual disability remains a hallmark but cannot be considered a mandatory diagnostic criterion of JS. Despite the high variability in the phenotypic spectrum and the extent of multiorgan involvement, nearly one quarter of JS patients had a favorable long‐term outcome with borderline cognitive deficit or even normal cognition. Most of JS population also showed relatively preserved communication skills and overall discrete behavioral functioning in everyday life, independently from the presence and/or level of intellectual disability. © 2016 Wiley Periodicals, Inc.